Strengthening Community Empowerment Through Business Legalization Assistance for MSMEs: Evidence from Panaikang Village, East Sinjai - Makmur; Sitti Fatimah; A. Fitriani; Mochamad Nurdin; Rusdiana; Muhammad Amar; Winadia; Asrul; Nurfadillah; Fajarudddin (www.amertainstitute.com, 2026)
Business legality is a crucial foundation for strengthening the identity, credibility, and competitiveness of micro, small, and medium enterprises (MSMEs), particularly in rural areas. Many MSME actors face obstacles in accessing formal legality due to limited knowledge and administrative capacity. This community service program aimed to empower MSMEs in Panaikang Village, East Sinjai District, through assistance in obtaining business legality, specifically the Business Identification Number (NIB) and Halal Certification. The program employed a participatory approach consisting of an initial survey, program socialization, data collection, training sessions, and direct assistance in issuing legal documents. The target group included MSME actors engaged in food processing, snacks, beverages, and local products. The results demonstrate a significant increase in participants’ understanding of the importance of business legality, product packaging, and basic marketing strategies. Most MSME actors successfully obtained their NIB, while several culinary businesses proceeded to the halal certification application stage. This assistance also enhanced entrepreneurs’ confidence and readiness to expand market access, including participation in local MSME exhibitions. The program contributed to strengthening local economic potential and promoting sustainable community-based economic development. Overall, business legality assistance proved to be an effective empowerment strategy for improving MSME resilience, formalization, and competitiveness in rural communities. Continuous collaboration between universities, local governments, and supporting institutions is recommended to ensure sustainability and broader impact.